DESIGNING A REPRESENTATION OF JAKARTA'S MARITIME CULTURAL IDENTITY AT THE EXHIBITION AREA MUSEUM BAHARI, JAKARTA - Faturohman, Firman; Soekardi, Kresno Yulianto (UI Scholars Hub, 2023)
This study describes the identity of Jakarta's maritime culture which is represented through the exhibition area at Museum Bahari. There are four maritime cultural identities of the maritime community in Jakarta that will be displayed in the exhibition area of the Museum Bahari, namely inclusive cultural identities, maritime knowledge, hardworking, and multiculturalism. The theme of the exhibition study on the cultural identity of the Jakarta maritime community was chosen because the current condition of the exhibition area of the Museum Bahari in Jakarta has not yet presented an exhibition area about Jakarta's marine life to accommodate visitors and the public, especially those from Jakarta and its surroundings. The research method used in this study is a qualitative research method. While the theory used in this research is the theory of cultural identity and the new museology paradigm that is oriented towards the community, which will then be applied to examine the exhibition system at the Museum Bahari. The research resulted in several exhibition themes that represent Jakarta's maritime identity which will then be presented in the exhibition area at the Museum Bahari by prioritizing education and entertainment for visitors and the public in the new museology paradigm.